(untitled) (Journal of Information Technologies in Education (ITE), 2018)
The article deals with the didactic issues of interactive learning environments development for ESP (English for special purposes) studying in virtual or augmented reality. It is proved that such educational environments as a means of students English-speaking professionally oriented educational activity organization has an active character, includes multimedia, is a professionally and communicatively designed course for ESP teaching and learning and corresponds to a combined type of computer programs. Issues of foreign language future users communicative language competence as a learning goal which can be realized on the condition of mastering in such types of speech activity as perception, production, interaction and mediation are considered. The system of training exercises is given taking into account the communicative activities interaction and instructions for their implementation into the conditions of an artificial (virtual or augmented reality) interactive educational environment are considered. The main instruments that should be implemented into the educational environment with the purpose of ESP study in a higher education establishment are identified. As a result of the experiment, it was revealed that out of nine exercises aimed at developing of ESP communication skills, five of them should contain tasks for listening, seven for speaking (monologic and dialogical), five for writing, three for reading, two of them should be on mediation. Such quantity of communicative exercises in combination with elements of computer games embedded in the educational environment and opportunities for students to design some educational elements (video, blogs, web pages, chats) independently provide a student-centric model of the learning process and have necessary motivation.